Prova e demonstração em Geometria Plana: concepções de estudantes da licenciatura em ensino de Matemática em Moçambique - Ordem, Jacinto (2015)
This research aims to analyze the conceptions of proof and demonstration in plane geometry among undergraduate students in mathematics teaching at Pedagogical University of Mozambique. It is a qualitative research whose data collecting procedure was based on a questionnaire and interviews. The questionnaire consisted of a sequence of tasks requiring the production of proofs and demonstrations, and the evaluation of methods of proofs by the subjects, at first. In a second step, the same subjects are interviewed about their own productions their responses. To carry out this part of study, each subject talks with the researcher about what he/she did, seeing to understand in depth the sense of his/her productions. This data collecting, articulating the questionnaire and the interviews, that we call triangulation of method, a terminology borrowed from Araújo and Borba (2006). Attended the research 19 prospective teachers in their 4th year of training in Mathematics Teaching, for final series of basic education Secondary education from Nampula and Beira Campus. Yet, took part of methodological procedures the didactical analyzes (a priori and a posteriori analyzes) of tasks designed for the questionnaire. As a theoretical framework of the study, we used the ideas of Paradigms and Geometrical Workspace proposed by Houdement and Kuzniak; the Type of Proofs, proposed by Balacheff, and Proof Schemes advanced by Harel and Sowder. The analysis of results showed that: (i) the subjects did not show consistent strategies of production of demonstrations, nor justifications with plausible mathematical foundation their strategies seem to be more influenced by didactical textbooks adopted in elementary school geometry. (ii) the subjects deal with proofs and demonstrations another topic of mathematics learning and not as means of communication and mathematical validation. (iii) the subjects do not use consistent criteria for evaluate proofs and demonstrations. (iv) our subjects have conception that proof and demonstration are simple rituals dissociated from one of its main roles, that of validating true properties and conjectures, or rejecting false conjectures. The study also showed that among subjects, reins the conception that there are empirical methods that validate geometrical properties, even if they are not demonstrations, and empirical methods that do not validate geometrical properties, depending on the type instrument used. In our perspective, we can say that this research is a valuable contribution to Mathematics Education, in general, and, particularly to the Mozambican context, if we consider that research of this kind is scarce in Mozambique. Therefore, we believe that the results of the study may contribute to rethink about the way geometry is seen at Pedagogical University of Mozambique